2022
DOI: 10.1038/s41598-022-14907-2
|View full text |Cite
|
Sign up to set email alerts
|

Electron beam surface remelting enhanced corrosion resistance of additively manufactured Ti-6Al-4V as a potential in-situ re-finishing technique

Abstract: This study explores the effect of surface re-finishing on the corrosion behavior of electron beam manufactured (EBM) Ti-G5 (Ti-6Al-4V), including the novel application of an electron beam surface remelting (EBSR) technique. Specifically, the relationship between material surface roughness and corrosion resistance was examined. Surface roughness was tested in the as-printed (AP), mechanically polished (MP), and EBSR states and compared to wrought (WR) counterparts. Electrochemical measurements were performed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 74 publications
(149 reference statements)
0
8
0
Order By: Relevance
“…screws and plates) fabricated with these alloys are used for temporary fixation of fractured bone; however, a second surgery is required to remove the temporary implants [1]. Localized cell death, excessive fibrotic tissue formation, and longlasting inflammation can also result from the release of toxic metals from metallic biomaterials, such as Ni, Cr, V, and Co [3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…screws and plates) fabricated with these alloys are used for temporary fixation of fractured bone; however, a second surgery is required to remove the temporary implants [1]. Localized cell death, excessive fibrotic tissue formation, and longlasting inflammation can also result from the release of toxic metals from metallic biomaterials, such as Ni, Cr, V, and Co [3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…By examining the SKPFM map in Figure d, it is evident that the LSP phases exhibit a higher electrical surface potential compared to the α-Mg (matrix). This observation holds true even when considering the negligible influence of differences in surface roughness on the surface potential values. , Furthermore, SEM/EDXS maps confirm the presence of small-sized, bright spots with the highest surface potential, which align with the Zr-rich regions.…”
Section: Resultsmentioning
confidence: 65%
“…This observation holds true even when considering the negligible influence of differences in surface roughness on the surface potential values. 42 , 43 Furthermore, SEM/EDXS maps confirm the presence of small-sized, bright spots with the highest surface potential, which align with the Zr-rich regions.…”
Section: Resultsmentioning
confidence: 87%
“…Interestingly, Shahsavari et al [154] found that corrosion resistance in AM Ti-6Al-4V is improved with decreasing surface roughness, which can be achieved using techniques such as electron beam surface remelting. However, this may be undesirable as a decreased surface roughness will be detrimental in aiding bone ingrowth and decrease bone adhesion.…”
Section: Wear In Am Latticesmentioning
confidence: 99%
“…This is mainly owing to the increased surface roughness in AM Ti–6Al–4V components. The inherent irregularities on the surface of AM components are due to the solidification of the melt pool, leading to partially melted powder particles [153] on the component surface, which are in the range of 10–60 μ m in diameter for SLM powders and 50–150 μ m for EBM powders [154]. Furthermore, the layer-by-layer deposition in AM causes surface defects such as the stair-step effect [155].…”
Section: Wearmentioning
confidence: 99%